Investing in the Future: A Role for Professional Societies to Prepare the Next Generation of Healthcare Leaders Through Curriculum Development and Dissemination. (17th March 2021) - Luther, Vera P; Shnekendorf, Rachel; Logan, Ashleigh; Advani, Sonali D; Barsoumian, Alice E; Beeler, Cole; Bennani, Kenza; Cherabuddi, Kartikeya; Holubar, Marisa; Huang, Misha; Ince, Dilek; Justo, Julie Ann; et al.
Abstract: Professional societies serve many functions that benefit constituents; however, few professional societies have undertaken the development and dissemination of formal, national curricula to train the future workforce while simultaneously addressing significant healthcare needs. The Infectious Diseases Society of America (IDSA) has developed 2 curricula for the specific purpose of training the next generation of clinicians to ensure the future infectious diseases (ID) workforce is optimally trained to lead antimicrobial stewardship programs and equipped to meet the challenges of multidrug resistance, patient safety, and healthcare quality improvement. A core curriculum was developed to provide a foundation in antimicrobial stewardship for all ID fellows, regardless of career path. An advanced curriculum was developed for ID fellows specifically pursuing a career in antimicrobial stewardship. Both curricula will be broadly available in the summer of 2021 through the IDSA website. Graphical Abstract: